An investigation into the implementation of Computer-Assisted Education (CAE) in the underprivileged areas of the Eastern Cape : a case study of Butterworth High School - Cronje, Johannes Christoffel (University of Pretoria, 2013)
Dissertation (MEd (Computer-Assisted Education))--University of Pretoria, 2006.